THE RELATIONSHIP BETWEEN SIMPLE SUGAR INTAKE AND THE ABDOMINAL CIRCUMFERENCE OF PSSK STUDENTS - Sharma, Ansehs; SUTADARMA, I WAYAN GEDE; SURUDARMA, I WAYAN; WIRYANTHINI, IDA AYU DEWI (E-Jurnal Medika Udayana, 2024)
The abdominal circumference is dependent upon various factors, one of it is the simple sugar intake. Hence, research has been conducted in order to determine the effects of simple sugar intake on the abdominal circumference because there is an increase in people who have a large abdominal circumference in the past years, mainly due to increase in simple sugar intake. The research was conducted using a descriptive design with a cross-sectional analytical research method amongst the Medical Students of Udayana University by providing questionnaires. For the majority of the students, the simple sugar intake appears to be in the mid-range. There are 15 students, whose intake is more than the mid-range and 14 student whose intake below the mid-range. For majority of students, the abdominal circumference appears to be around the mid-range, 65.8cm to 92.8cm. There are 8 students whose abdominal circumference is more than the mid-range and another 8 students whose abdominal circumference is below the mid-range. The Pearson chi-square test value is 25.772 with an asymptotic significance 2 tailed (often referred to as “p”, short for probability) value of 0.018. Since this p-value is below 0.05, it means there is a significant or valid relationship between the two variables as expected.In conclusion, there is a significant relationship and moderate correlation between the intake of simple sugars and abdominal circumference amongst the PSSK UNUD students